Preliminary evidence of transient fatigue and pacing during interchanges in rugby league - Waldron, M.; Highton, J.; Daniels, M.; Twist, C. (International Journal of Sports Physiology and Performance, 2013)
Purpose: This study aimed to quantify changes in heart rate (HR) and movement speeds in interchanged and whole-match players during 35 elite rugby league performances. Methods: Performances were separated into whole match, interchange bout 1, and interchange bout 2 and further subdivided into match quartiles. Mean percentages of peak HR (%HRpeak) and total and high-intensity running (> 14 km/h) meters per minute (m/ min) were recorded. Results: For whole-match players, a decline in high-intensity m/min and %HRpeak was observed between successive quartiles (P < .05). High-intensity m/min during interchange 1 also progressively declined, although initial m/min was higher than whole match (24.2 ± 7.9 m/min vs 18.3 ± 4.7 m/min, P = .018), and %HRpeak did not change over match quartiles (P > .05). During interchange 2, there was a decline in high-intensity m/min from quartile 1 to quartile 3 (18 ± 4.1 vs 13.4 ± 5 m/min, P = .048) before increasing in quartile 4. Quartiles 1 and 2 also showed an increase in %HRpeak (85.2 ± 6.5 vs 87.3 ± 4.2%, P = .022). Conclusions: Replacement players adopted a high initial intensity in their first match quartile before a severe decline thereafter. However, in a second bout, lower exercise intensity at the outset enabled a higher physiological exertion for later periods. These findings inform interchange strategy and conditioning for coaches while also providing preliminary evidence of pacing in team sport.